Answer:
2.5
Step-by-step explanation:
……..,,….,,,,…………,,,,,,…….
oksian1 [2.3K]
Ey kamusta kana bat ka nandito?
Answer:
![7x + 3y- 2+6x-1+y^2 = y^2+ 3y+13x- 3](https://tex.z-dn.net/?f=7x%20%2B%203y-%202%2B6x-1%2By%5E2%20%3D%20y%5E2%2B%203y%2B13x-%203)
Step-by-step explanation:
Given
![7x + 3y- 2+6x-1+y^2](https://tex.z-dn.net/?f=7x%20%2B%203y-%202%2B6x-1%2By%5E2)
Required
Simplify
Start by collecting like terms
![7x + 3y- 2+6x-1+y^2 = y^2+ 3y+7x +6x- 2-1](https://tex.z-dn.net/?f=7x%20%2B%203y-%202%2B6x-1%2By%5E2%20%3D%20y%5E2%2B%203y%2B7x%20%2B6x-%202-1)
Simplify like terms
![7x + 3y- 2+6x-1+y^2 = y^2+ 3y+13x- 3](https://tex.z-dn.net/?f=7x%20%2B%203y-%202%2B6x-1%2By%5E2%20%3D%20y%5E2%2B%203y%2B13x-%203)
Answer:
56 degrees
Step-by-step explanation:
The midsegment is parallel to a side and the other side is a transversal. Using the Corresponding Angles Theorem, you get that m<1=56 degrees